2017
DOI: 10.4142/jvs.2017.18.4.499
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopic characteristics of tracheal collapse and cervical lung herniation in dogs: 222 cases (2012–2015)

Abstract: This retrospective study included 222 dogs suspected to have tracheal collapse (TC) and examined between 1 January 2012 and 31 December 2015. Fluoroscopic and radiographic images and medical records were evaluated to investigate the fluoroscopic characteristics of TC and cervical lung herniation (CLH), and to determine their relationships to various influencing. Grade of TC, existence of tracheal kinking, location of CLH (right or left side), and grade of CLH were evaluated fluoroscopically. One hundred ninety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Bronchomalacia, defined as collapse of segmental/subsegmental airways [ 1 ], tends to be diffuse and may also have a marked impact on lung function. While tracheal and mainstem bronchial collapse is prevalent in middle-aged to old dogs weighing less than 10 kg [ 2 , 3 , 4 ], bronchomalacia, which is defined herein, affects dogs of all ages and weights [ 3 ]. In contrast, lobar bronchial collapse is frequently anatomically limited (e.g., only affecting one or few lobar bronchi) or has a minimal reduction in the airway caliber and contribution to the clinical signs and functional impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Bronchomalacia, defined as collapse of segmental/subsegmental airways [ 1 ], tends to be diffuse and may also have a marked impact on lung function. While tracheal and mainstem bronchial collapse is prevalent in middle-aged to old dogs weighing less than 10 kg [ 2 , 3 , 4 ], bronchomalacia, which is defined herein, affects dogs of all ages and weights [ 3 ]. In contrast, lobar bronchial collapse is frequently anatomically limited (e.g., only affecting one or few lobar bronchi) or has a minimal reduction in the airway caliber and contribution to the clinical signs and functional impairment.…”
Section: Introductionmentioning
confidence: 99%
“…In fluoroscopy, views were obtained with the patient in lateral and ventro-dorsal recumbency with a regular respiration phase and a forceful expiration phase. In addition to being used to diagnose TC and indicate the locations and gradings of TC in each area, fluoroscopy was also used to determine if there was lung herniation based on induced coughing in a humanoid position [6]. TC was evaluated in four regions (cervical, thoracic inlet, intrathoracic, and carinal regions) and was graded by measuring the decrease in luminal diameter: less than 25% (Grade 1), 25% to < 50% (Grade 2), 50% to 75% (Grade 3), and more than 75% (Grade 4) [2671116].…”
Section: Methodsmentioning
confidence: 99%
“…Canine tracheal collapse (TC) is a chronic, primary disease of the respiratory tract. The disease is characterized by tracheobronchomalacia with weakened and flattened C-shaped cartilage [12345], which is accompanied by narrowing of the tracheal lumen and muscle prolapse of the dorsal trachea [267]. TC occurs mainly in middle-aged to older, overweight, and small-breed dogs [248].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, cervical lung hernia was known as a rare phenomenon in dogs [ 13 ]. However, the study of Lee et al [ 14 ] reported that cervical lung hernia is finally a common finding in older dogs. No surgical management has been performed in these cases.…”
Section: Discussionmentioning
confidence: 99%